Application of New Materials in Auditory Disease Treatment - Li, Ming; Mu, Yurong; Cai, Hua; Wu, Han; Ding, Yanyan (Frontiers in Cellular Neuroscience, 2022)
Auditory diseases are disabling public health problems that afflict a significant number of people worldwide, and they remain largely incurable until now. Driven by continuous innovation in the fields of chemistry, physics, and materials science, novel materials that can be applied to hearing diseases are constantly emerging. In contrast to conventional materials, new materials are easily accessible, inexpensive, non-invasive, with better acoustic therapy effects and weaker immune rejection after implantation. When new materials are used to treat auditory diseases, the wound healing, infection prevention, disease recurrence, hair cell regeneration, functional recovery, and other aspects have been significantly improved. Despite these advances, clinical success has been limited, largely due to issues regarding a lack of effectiveness and safety. With ever-developing scientific research, more novel materials will be facilitated into clinical use in the future.